The Bending Behaviour of a ‘Reversed’ Profiled Steel Sheet Dry Board (PSSDB) Panel for Application in a Roofing System - Awang, Hanizam; Badaruzzaman, Wan Hamidon Wan (Penerbit Universiti Sains Malaysia, 2009)
Finite element modelling and experimental study of the structural behaviour involving the stiffness and strength of an innovative composite panel system known as the Profiled Steel Sheet Dry Board (PSSDB) system, to be applied as roofing units in buildings, is investigated in this paper. The system consists of profiled steel sheeting connected to dry board by self-drilling and self-tapping screws. This study considered the behaviour of the PSSDB panel under an out-of plane uniform load to understand the behaviour of the PSSDB panel when it is positioned in a ‘reversed’ position in order to make it more practical and applicable. In addition, the effect of introducing side timber strips along the edge side of the panel system is also studied. It is found that the timber strips increased the stiffness value from 57.6 kNm2 m–1 to 78.2 kNm2 m–1, i.e., an increase of 35.8% compared to panels without timber jointing strips. In fact, the maximum load that can be sustained by the connected panels was increased from 3.47 kN m–1 to 6 kN m–1. The finite element model developed has shown accuracy within 5% to 11% compared to experimental results in predicting the deflection of the PSSDB panel